2D and 3D homogenization and fracture analysis of concrete based on in-situ X-ray Computed Tomography images and Monte Carlo simulations. (September 2016) - Huang, Yujie; Yan, Dongming; Yang, Zhenjun; Liu, Guohua
Abstract: The homogenized elastic properties and tensile fracture behaviours of concrete are captured by Monte Carlo simulations (MCSs) of realistic meso-scale models based on high-resolution micro-scale X-ray Computed Tomography (XCT) images, using asymptotic homogenization and the concrete damaged plasticity (CDP) model. The obtained realistic models are quite promising in characterising meso-scale mechanical behaviours of concrete. The statistical analysis shows that the intrinsic heterogeneity of meso-structures caused by random spatial distribution of multi-phases can significantly affect macroscopic responses of concrete, e.g. homogenized elastic properties, crack patterns and load-carrying capacities. Moreover, since the 3D model is built from 2D images by a bottom-up stacking algorithm, the resultant 3D model is strongly correlated to the 2D models in physical nature, thus the 2D-3D comparisons can yield more insightful views. The effects of aggregate/void area fraction on homogenized elastic modulus and tensile strength are also analysed.